Optimization of spinning parameters on the fabrication of NH 2 -MIL-53(Al)/cellulose acetate (CA) hollow fiber mixed matrix membrane for CO 2 separation - Mubashir, M. (2019)
The attractive features of this work lies on the optimization of spinning parameters including, take-up speed and air-gap distance on the fabrication of NH 2 -MIL-53(Al)/CA Hollow fiber mixed matrix membranes (HFMMMs) for gases separation. The morphology and distribution of particles in the resultant HFMMMs were characterized by using FESEM and EDX mapping, respectively. FESEM images showed that the increase in take-up speed and air-gap distance reduced the outer diameters of HFMMMs from 275.5 Âµm to 110.1 Âµm and 719.1 Âµm to 648.4 Âµm, respectively. The gas permeation results exhibited that the permeance values were reduced and ideal selectivities were improved with the increment of take-up speed. Increasing trend of ideal selectivities could be because of progression of polymer orientation, packing and mono-disperse space which suppressed the non-selective voids and Knudsen pores in the HFMMMs. However, variation of air-gap distance produced âVâ and âAâ pattern for permeance and ideal selectivity values, respectively, for all HFMMMs spun at different take-up speeds. The HFMMM spun at optimum spinning condition at take up speed of 12.2 m/min and air gap distances of 5.0 cm showed the highest CO 2 /CH 4 ideal selectivity of 16.0 and CO 2 /N 2 ideal selectivity of 12.0. Hence, optimization of spinning parameters can be considered as feasible and efficient method in order to fabricate HFMMMs with higher separation performance. The enhanced CO 2 permeance and ideal selectivities demonstrated that NH 2 -MIL-53(Al)/CA HFMMM spun at optimum condition is potential for industrial gas separation. Â© 2018